2004
DOI: 10.1161/01.str.0000117575.48205.2d
|View full text |Cite
|
Sign up to set email alerts
|

Anticardiolipin Antibodies and Risk of Ischemic Stroke and Transient Ischemic Attack

Abstract: Background and Purpose-The role of anticardiolipin antibodies (aCLs) as novel risk factors for ischemic stroke and transient ischemic attacks (TIAs) has been a matter of debate. Prior cohort studies included only selected subjects, mostly men. We related serum concentrations of aCLs to incident first ischemic stroke/TIA among men and women in the Framingham Heart Study cohort and offspring. Methods-There were a total of 2712 women (mean age, 59.3 years) and 2262 men (mean age, 58.3 years) free of stroke/TIA at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 22 publications
1
69
0
8
Order By: Relevance
“…[689][690][691][692][693][694] In a case-control study of 255 patients with a mean age of 66 years, the presence of an anticardiolipin antibody was associated with a significantly increased risk for ischemic stroke (adjusted OR, 2.31; 95% CI, 1.09-4.90). 695 These findings were not replicated in a subsequent prospective cohort study that was part of WARSS.…”
Section: Antiphospholipid Antibodiesmentioning
confidence: 99%
“…[689][690][691][692][693][694] In a case-control study of 255 patients with a mean age of 66 years, the presence of an anticardiolipin antibody was associated with a significantly increased risk for ischemic stroke (adjusted OR, 2.31; 95% CI, 1.09-4.90). 695 These findings were not replicated in a subsequent prospective cohort study that was part of WARSS.…”
Section: Antiphospholipid Antibodiesmentioning
confidence: 99%
“…621 The study included 2712 women (mean age, 59.3 years) and 2262 men (mean age, 58.3 years) who were free of stroke or TIA at the time of their baseline examination. An enzyme-linked immunosorbent assay (ELISA) was used to measure aCL from stored frozen sera.…”
Section: Hypercoagulabilitymentioning
confidence: 99%
“…The prevalence of stroke in Nigeria is on the increase.6, 7 Osuntokun et al6 reported a crude prevalence of 58 per 100,000 of the population and Danesi et al 7 in a more recent studies reported a rate of 1.14 per 1,000. It is principally a disease of the elderly 8 however there is an increase in the prevalence of stroke in younger age group 9,10 . Stroke is a devastating event because of the consequent physical and psychological stress, economic loss to families and to the nation especially when young people are affected.…”
Section: Introductionmentioning
confidence: 99%